O gênero Meteorus (Hymenoptera, Braconidae) na região neotropical: um estudo integrativo - Almeida, Luis Felipe Ventura de (Universidade Federal de São Carlos, 2022)
Species are one of the fundamental components of biodiversity. Their correct identification is essential for several areas of biological research such as ecological modeling, pest control and the development of conservation strategies. Despite more than two centuries of taxonomic research most species are still unknown to science. This fact is especially evident in certain megadiverse and historically understudied groups, such as parasitoid wasps. These insects can directly affect the populations of their hosts and have great ecological and economic relevance. Meteorus (Hymenoptera, Braconidae) is a cosmopolitan genus, with over 350 known species, and develops as a koinobiont endoparasitoid of Coleoptera and Lepidoptera larvae, including several agricultural pests. However, this group is still poorly studied in the Neotropical region. In this work, 1,366 specimens belonging to the genus Meteorus, collected in Brazil and Costa Rica, were examined. Fifty-five species were identified in the material studied, among which 36 are considered new to science and described. Molecular data from the COI marker and host records for several of the species studied are included. A dichotomous key for the species recorded in Brazil is presented. The phylogenetic analysis performed corroborates previous works in recovering the genus Zele as a derived lineage from Meteorus and its reclassification is suggested. A new clade with neotropical distribution is identified, corresponding to species related to M. papiliovorus, which is defined primarily by the presence of a carina in the ventro-posterior region of the mesopleuron. Host utilization data demonstrated the presence of a high degree of specialization in the genus, which contrasts with previous records, and especially with what has been described for species with economic relevance. Currently available data suggests that the neotropical species regarded as generalists could represent complexes of cryptic species. The combined use of morphological, molecular and ecological data proved to be relevant for the definition of the species studied here and will likely be essential for the resolution of taxonomic questions still present in the genus.
The genus Meteorus (Hymenoptera, Braconidae) in the neotropical region: an integrative study
Keywords: Taxonomia; Biodiversidade; Parasitoide; Ichneumonoidea; Hymenoptera; Vespas; COI; Hospedeiro; Euphorinae; Taxonomy; Biodiversity; Parasitoid; Wasp; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS; CIENCIAS BIOLOGICAS::ZOOLOGIA::TAXONOMIA DOS GRUPOS RECENTES